Global health and care worker migration requires a global response - Kuhlmann, Ellen; Falkenbach, Michelle; Correia, Tiago; Humphries, Niamh; Hutchinson, Eleanor; Rees, Gareth H; Ungureanu, Marius-Ionut; Zapata, Tomas; Lohmann, Julia (Health policy, 2025)
The global migration of the health and care workforce (HCWF) has intensified, leading to complex policy scenarios and diverse migration patterns. While the traditional narrative of individual health and care workers (HCWs) migrating from low- and middle-income countries to high-income countries in search of higher income, career prospects and working conditions remains relevant, it now coexists with many other drivers, incentives, and dynamics at individual and policy level. The evolving dynamics of HCW migration have profound implications extending far beyond health labour markets, influencing broader societal and political landscapes. Despite their significance, the qualitative shifts in HCWF migration patterns and the governance challenges they present are poorly understood and under-researched, and policies have thus been limited in their effectiveness. In this policy comment we argue for a global response and an enhanced focus on policy implementation, using selected case studies to illustrate the argument. The cases highlight complexities of HCW migration patterns and opportunities for strengthening implementation of the WHO Global Code of Practice to respond effectively to the diverse needs of health systems and individual HCWs.
Online verfügbar 28 March 2025, Version des Artikels 3 April 2025
Gesehen am 10.10.2025